The morphological and phytochemical studies on the effect of acute and recurrent irradiation in Celosia cristata seeds (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Aisyah SI, Muhallilin I, Sukma D, Nurcholis W. 2019. The morphological and phytochemical studies on the effect of acute and recurrent irradiation in Celosia cristata seeds. Biodiversitas 20: 3766-3771. The present work investigated the agro-morphological changes in Celosia cristata L. seeds exposed to gamma irradiations. This study also conducted phytochemical screening to screened secondary metabolite change in C. cristata. C. cristata seeds were irradiated with acute radiation at doses of 470, 480, and 490 Gy and were planted until M1 generation. Recurrent irradiation was done on M1 seeds at a dose of 250 Gy. The agro-morphological and phytochemical diversity was performed in M2 generation. The highest difference characters in acute irradiated plants were found on plant height, number of branches, and flower length, while the plant diameter, flower width, and number of flowers were found the highest in recurrent irradiation. Agro-morphological important changes in recurrent irradiated plants were decreased plant height and increased the number of flowers that compared with acute irradiated and control plants. The qualitative phytochemical showed no difference between acute and recurrent irradiated plants. It can be concluded that the recurrent irradiated changes the morphological valuable of C. cristata, while the phytochemical is needed further research.
Keywords: Celosia cristata, mutation, gamma radiation, acute radiation, recurrent irradiation